NIMG-11. IMPACT OF INVERSION TIME FOR FLAIR ACQUISITION ON THE T2-FLAIR MISMATCH DETECTABILITY FOR IDH-MUTANT, NON-CODEL ASTROCYTOMAS. (9th November 2020) - Kinoshita, Manabu; Arita, Hideyuki; Takahashi, Masamichi; Uda, Takehiro; Fukai, Junya; Ishibashi, Kenichi; Kijima, Noriyuki; Hirayama, Ryuichi; Sakai, Mio; Arisawa, Astuko; Takahashi, Hiroto; Nakanishi, Katsuyuki; et al.
Abstract: PURPOSE: The current research tested the hypothesis that TI shorter than 2400 ms under 3T for FLAIR can improve the diagnostic accuracy of the T2-FLAIR mismatch sign for identifying IDH mt, non-CODEL astrocytomas. EXPERIMENTAL DESIGN: We prepared three different cohorts; 94 MRI from 76 IDH mt, non-CODEL LrGGs, 33 MRI from 31 LrGG under the restriction of FLAIR being acquired with TI < 2400 ms for 3T or 2016 ms for 1.5T, and 103 MRI from 103 patients from the TCIA/TCGA dataset for LrGG. The presence or absence of the "T2-FLAIR mismatch sign" was evaluated, and we compared diagnostic accuracies according to TI used for FLAIR acquisition. RESULTS: The T2-FLAIR mismatch sign was more frequently positive when TI was shorter than 2400 ms under 3T for FLAIR acquisition ( p = 0.0009, Fisher's exact test). The T2-FLAIR mismatch sign was positive only for IDH mt, non-CODEL astrocytomas even if we confined the cohort with FLAIR acquired with shorter TI ( p = 0.0001, Fisher's exact test). TCIA/TCGA dataset validated that the sensitivity, specificity, PPV, and NPV of the T2-FLAIR mismatch sign to identify IDH mt, non-CODEL astrocytomas improved from 31%, 90%, 79%, and 51% to 67%, 94%, 92%, and 74%, respectively if we acquired FLAIR with TI shorter than 2400 ms. CONCLUSIONS: We revealed that TI for FLAIR impacts diagnostic accuracy of the T2-FLAIR mismatch sign and that FLAIR scanned with TI < 2400 ms in 3T is necessary for LrGG imaging.